RANCANG BANGUN APLIKASI UNTUK MENINGKATKAN EFISIENSI LAYANAN CREATIVE AGENCY DI SWIFT IMPACT - Amanda, Risky; Alfannisa Annurrullah Fajrin (LPPM Universitas Putera Batam, 2024)
The creative industry makes a significant contribution to the global economy through technology, globalization, and changing consumer preferences. It includes film production, music, fashion, publishing, and digital creative services. However, creative agencies often face challenges in providing efficient services to clients, which can reduce satisfaction. To address this, the project proposes developing a digital creative agency application on the Android platform to enhance digital service efficiency with innovative solutions for service ordering.